Serbia and Montenegro : Fourth Review Under the Extended Arrangement (EA), Financing Assurances Review, Request for Waivers, and Modification of an end-December 2004 Performance Criterion. (IMF Staff Country Reports; Country Report, 2005)
The Fourth Review Under the Extended Arrangement, Financing Assurances Review, and Request for Waiver of Performance Criteria for Serbia and Montenegro are discussed. The agreed tighter fiscal, monetary, and incomes policies should cool off wage and credit growth, which are driving the demand for imports. The bold resumption of structural reforms should over time help increase exports, which remain exceptionally low in reference to GDP. The fragile political situation could affect the ability of the reformist minority government to press ahead with bold reforms.